Performance study of WiMAX mesh networks - Huang, Albert Enyao. (2009)
The IEEE 802.16 standard has defined two modes of operation: Point-to-Multipoint as well as Mesh mode. The mesh mode enables better scalability and enhanced coverage as the network topology is able to support traffic relay functions. Capabilities of the WiMAX Mesh network and methods to improve the performance of the network need to be examined as they are loosely defined in the standards. Close attention would be paid on areas of Quality-of-Service (QoS) provisioning as well as traffic relay issues in order to take full advantage of the network for optimum performance.